Eco-friendly hotel stay and environmental attitude: A value-attitude-behaviour perspective. (January 2022) - Sadiq, Mohd; Adil, Mohd; Paul, Justin
Abstract: The growing body of literature around eco-friendly hotels indicates an increase in popularity for such hotels. However, the low booking rate in eco-friendly hotel is a major concern for sustainability and profitability. Therefore, the current study addresses the long-lasting attitude-behaviour gap by investigating the role of environmental concern (altruistic values), health concern (egoistic values), environmental attitude, and service quality on increasing the tourists' eco-friendly behaviour. The model and hypotheses were tested using a two-step approach of structural equation modelling on 450 responses collected from Indian travellers through Amazon Mechanical Turk. The findings suggest that the environmental concern and the health concern are important factors in determining tourists' eco-friendly behaviour. Additionally, service quality emerged as a key factor in bridging the attitude-behaviour gap in the eco-friendly hotel context. Our findings provide insightful implications for hospitality managers, practitioners and policymakers in devising effective marketing strategies. Highlights: The value-attitude-behaviour model is expanded to investigate eco-friendly behaviour. Travellers egoistic as well as altruistic values positively recognise the eco-friendly behaviour. Environmental attitude partially mediates the relationship of eco-friendly behaviour with egoistic and altruistic values. Service quality positively moderate the relationship between environmental attitude and eco-friendly behaviour.